Adolescent Conflict and Young Adult Couple Relationships: Directionality of Violence - Susana Gaspara Paíno Quesada (Universidad de San Buenaventura, 2020)
The objective of this research was to study victimization and aggression in adolescent and young couple relationships, as well as to identify the directionality of violence perpetration in a sample of 984 people between 15 and 31 years of age, of which 58.2% were women and 41.8% were men. Regarding the educational level of the population under study, 26% were students of junior high school, senior high school, or vocational training and 56.5% were college students. The research design followed the nonprobability purposive sampling method and used the DVQ-R questionnaire. The results suggest that violence is 65.2% bidirectional and 14.30% unidirectional, being bidirectionality more frequent in psychological violence and decreasing when physical violence occurs. The results reveal the need to integrate the different modalities of dating violence (unidirectional and bidirectional) and unperceived violence –that gives rise to technical abuse– into the different prevention programs addressed to adolescents and youth.